The role of androgen and its related signals in PCOS - Ye, Wenting; Xie, Tingting; Song, Yali; Zhou, Lili (Journal of cellular and molecular medicine, 2021)
Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women at reproductive age. However, the underlying pathogenic mechanisms have not been completely understood. Hyperandrogenism is an important clinic feature in patients with PCOS, suggesting its pathologic role in the development and progression of PCOS. However, the actual role of androgen and the related signals in PCOS and PCOS‐related complications have not yet been clarified. In this review, we surveyed the origin and effects of androgen on PCOS and the related complications, highlighted the cellular signals affecting androgen synthesis and summarized the pathological processes caused by hyperandrogenism. Our review well reveals the important mechanisms referring the pathogenesis of PCOS and provides important clues to the clinic strategies in patients with PCOS.